2016
DOI: 10.1016/j.soilbio.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide uptake in rewetted wetlands with contrasting soil organic carbon contents

Abstract: a b s t r a c tRewetting drained peatlands creates favorable reduced conditions for denitrification, but, the potential of restored peatlands to act as N 2 O sink is poorly characterized. We monitored N 2 O emissions in rewetted peatlands converted to rice paddies with a range of soil organic carbon (SOC) (6%, 11%, and 23%) during the growing season. Negative N 2 O emissions were repeatedly observed in all sites, which were not affected by nitrogen fertilization at 80 kg N ha À1 . The highest consumption rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Net N 2 O flux averaged −0.51 g CO 2eq m −2 d −1 among all sites during this week of peak productivity. The process of atmospheric N 2 O removal is not clearly understood, but others have also observed N 2 O uptake during daylight hours (Yu et al 2012) and not during night hours (Ye and Horwath 2016). With the high detection limit of our equipment to track incremental changes over the 16 minute deployments, N 2 O uptake was distinguishable, and strongly correlated with PAR and air temperature (SI table 2).…”
Section: Resultsmentioning
confidence: 79%
“…Net N 2 O flux averaged −0.51 g CO 2eq m −2 d −1 among all sites during this week of peak productivity. The process of atmospheric N 2 O removal is not clearly understood, but others have also observed N 2 O uptake during daylight hours (Yu et al 2012) and not during night hours (Ye and Horwath 2016). With the high detection limit of our equipment to track incremental changes over the 16 minute deployments, N 2 O uptake was distinguishable, and strongly correlated with PAR and air temperature (SI table 2).…”
Section: Resultsmentioning
confidence: 79%
“…One potential source of concern are the negative N 2 O fluxes that we documented here. While some investigators have attributed negative fluxes to instrumental error (Cowan et al, 2014;Chapuis-Lardy et al, 2007), others have demonstrated that N 2 O consumption -particularly in wetland soils -is not an experimental artifact but occurs due to the complex effects of redox, organic carbon content, nitrate availability, and soil transport processes on denitrification (Ye and Horwath, 2016;Yang et al, 2011;Wen et al, 2016;Schlesinger, 2013;Teh et al, 2014;Chapuis-Lardy et al, 3680 Y. A. Teh et al: Seasonal variability in methane and nitrous oxide fluxes from tropical peatlands 2007).…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%
“…A. Teh et al: Seasonal variability in methane and nitrous oxide fluxes from tropical peatlands 2007). Given the low redox potential and high carbon content of these soils, it is plausible that microbial N 2 O consumption is occurring, because these types of conditions have been found to be conducive for N 2 O uptake elsewhere (Ye and Horwath, 2016;Teh et al, 2014;Yang et al, 2011).…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%
“…One potential source of concern are the negative N 2 O fluxes that we documented here. While some investigators have attributed negative fluxes to instrumental error (Cowan et al, 2014;Chapuis-Lardy et al, 2007), others have demonstrated that N 2 O consumptionparticularly in wetland soils -is not an experimental artifact, but occurs due to the complex effects of redox, organic carbon content, nitrate availability, and soil transport processes on denitrification (Ye and Horwath, 2016;Yang et al, 2011;Wen et al, 2016;Schlesinger, Biogeosciences Discuss., doi:10.5194/bg-2017-48, 2017 Manuscript under review for journal Biogeosciences Discussion started: 24 February 2017 c Author(s) 2017. CC-BY 3.0 License.…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%
“…Teh et al, 2014;Chapuis-Lardy et al, 2007). Given the low redox potential and high carbon content of these soils, it is plausible that microbial N O consumption is occurring, because these types of conditions have been found to be conducive for N 2 O uptake elsewhere (Ye and Horwath, 2016;Teh et al, 2014;Yang et al, 2011).…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%